Cys327Cys polymorphism of the PAPP-A gene (pregnancy associated plasma protein A) is related to mortality of long term hemodialysis patients - Kalousová, Marta; Jáchymová, Marie; Muravská, Alexandra; Kuběna, Aleš A; Dusilová-Sulková, Sylvie; Tesař, Vladimír; Zima, Tomáš (Clinical biochemistry, 2014)
OBJECTIVES: PAPP-A is an independent mortality predictor of long term hemodialysis patients and a prognostic marker of acute coronary syndrome in general population. Cys327Cys PAPP-A polymorphism (SNP) (rs12375498) was found to be of significance in preeclampsia and the C allele of the PAPP-A C/G SNP (rs13290387) was defined as an independent risk factor for acute myocardial infarction. The aim of the study was to test the role of these PAPP-A SNPs in long term hemodialysis patients. DESIGN AND METHODS: The studied group consisted of 464 subjects - 319 long term hemodialysis patients (183 men, 136 women, 62±14years) and 145 controls (65 men, 80 women, 49±14years). A subgroup of 211 hemodialysis patients (118 men, 93 women, 63±13years) was prospectively followed up for 4.5years. During the follow up, 111 patients died, 51 of them due to cardiovascular events. PAPP-A SNPs were analyzed by DNA sequencing and serum PAPP-A was measured by TRACE. RESULTS: Both SNPs were in Hardy-Weinberg equilibrium. Allelic and genotype frequencies did not differ between patients and controls and were not related to serum PAPP-A concentrations. Cys327Cys SNP was significant for patients' survival (HR (95% CI): 1.616 (1.110-2.353), nominal p=0.012, corrected p=0.036) while C/G SNP was not. CONCLUSIONS: Our study shows for the first time the significance of Cys327Cys PAPP-A SNP (rs12375498) for overall mortality of long term hemodialysis patients. Although it does not influence the concentration of PAPP-A it still could affect the correct function of this enzyme which has to be clarified in further studies.
Keywords: těhotenský plazmatický protein A; Polymorphism, Genetic; Renal Dialysis; Acute Coronary Syndrome; jednonukleotidový polymorfismus; rizikové faktory; genotyp; Polymorphism, Single Nucleotide; Humans; akutní koronární syndrom; dialýza ledvin; Genotype; lidé; polymorfismus genetický; Pregnancy-Associated Plasma Protein-A; Risk Factors